Eretrian ceramic products through time: Investigating the early history of a Greek metropolis. (June 2016) - Charalambidou, X.; Kiriatzi, E.; Müller, N.S.; Georgakopoulou, M.; Müller Celka, S.; Krapf, T.
Abstract: Eretria, an important ancient Greek polis with a rich Bronze Age past, was among the first colonial and commercial powers in the ancient world that founded already in the 8th c. BC a number of colonies and trading posts across the Aegean and the Mediterranean. In the context of a diachronic investigation of Eretrian pottery production and supply from the Early Bronze Age to the Roman period, a large number of pottery samples and geological materials have been analysed. The current article summarises the results of the analyses of the Bronze Age pottery from the site, comprising 151 pottery samples carefully selected from stratified deposits, which have been examined through petrographic and chemical (WD-XRF) analyses and compared to geological materials and experimental ceramic briquettes. Overall, the current evidence for local pottery production indicates that during the third and the early second millennia BC no dramatic change occurred in the exploitation of raw materials in Eretria for pottery production, in spite of conspicuous stylistic and technological transformations. The first possible change in raw material sources, which occurs in the Middle Helladic period and affects coarse wares only, corresponds with a major break in the site occupation. Unlike local products, most imported fabrics do not show continuity through time, indicating changes in the direction of external relationships in Eretria. Highlights: We summarise the analyses' results of Bronze Age pottery from Eretria (Euboea). This research programme combines macroscopic, petrographic and chemical analyses. No dramatic changes occur in raw material exploitation for local pottery production. The first possible change in raw material choices occurs in the Middle Helladic period. Most imported fabrics do not show continuity through time.